Cinnamon Sugar Scrub Dermatitis: "Natural" Is Not Always Best. Issue 1 (4th October 2016) - Admani, Shehla; Hill, Hannah; Jacob, Sharon E.
Abstract: Children are at risk of developing allergic contact dermatitis to fragrances. Personal hygiene products, even those labeled hypoallergenic or considered all natural, may be a significant source of fragrance exposure in this population.